Urban Creative Tourism As An Effort To Improve The Economy of The Batu Malang Tourism City Area - Budi Prawoto (Journal Research of Social Science, Economics, and Management, 2022)
Cities in a country have become a major actor that is more prominent than the country itself in regional and even global geographical relations. Competition between cities to gain trust as the best city in a particular aspect depends on how the city can convey the strength of competition with the relevance of the city. However, the competition is not only between baser cities, but also baser cities and ceci cities. So a strategy is needed for small cities to be able to increase their competitiveness in order to compete with big cities through city branding. Regional competitiveness is one of the main issues in regional developmentThe analysis method used in this study is descriptive analysis (descriptive research) using qualitative and quantitative approaches. Hasil this research, among others 1) In general, the results of this study are expected to provide recommendations for the government, especially the Batu City Government and other actors involved in the impact of creative tourism in Batu City. 2) This research is expected to be used as a strategy to implement creative tourism development in Batu City properly and sustainably. 3) In addition, this research also aims to provide academic knowledge related to creative tourism in Indonesia in general and in Batu City in particular. Creative Tourism aims to bind the soul of tourists to the attractiveness of tourism. The process of soul engagement and authentic experiences owned by each individual tourist is an important point in the development of tourism. With this new marketing pattern, it inspired many local governments, to apply it in the development of the image of their city. The development of tourism in the form of creative tourism is considered to be able to lift and shape the image of a city with increasing visits and consumption of tourist products with creative types of tourism.